Current development and dissemination of computer... - Adirim, I. (Soviet Studies, 1991)
Assesses the state of computer technology in the Union of Soviet Socialist Republics (USSR). Changes in research and development of computer technology in USSR; Data on the backwardness of computer technology in USSR; General assessment on the computer technology.